Predictors of pulmonary sequelae after COVID-19 pneumonia: A 12-month follow-up study - Bernardinello, Nicol; Cocconcelli, Elisabetta; Giraudo, Chiara; Daverio, Matteo; Castelli, Gioele; Petrarulo, Simone; Bovo, Matteo; Fichera, Giulia; Cavinato, Silvia; Cattelan, Anna Maria; Saetta, Marina; Spagnolo, Paolo; et al. (Frontiers in Medicine, 2023)
Background: since the beginning of the SARS-CoV-2 pandemic, over 550 million people have been infected worldwide. Despite these large numbers, the long-term pulmonary consequences of COVID-19 remain unclear. Aims: the aim of this single-center observational cohort study was to identify and characterize pulmonary sequelae of COVID-19 at 12 months from hospitalization and to reveal possible predictors for the persistence of long-term lung consequences. Methods: based on the persistence or absence of radiological changes after 12 months from hospitalization, the whole population was categorized into NOT-RECOVERED (NOT-REC) and RECOVERED (REC) groups, respectively. Clinical and pulmonary function data tests and clinical data were also collected and compared in the two groups. In the NOT-REC group, High Resolution Computed Tomography images were semiquantitatively scored analyzing ground-glass opacities (GGO), interstitial thickening (IT), consolidations (CO), linear and curvilinear band opacities, and bronchiectasis for each lung lobe. Logistic regression analyses served to detect the factors associated with 12-months radiological consequences. Results: out of the 421 patients followed after hospitalization for SARS-CoV-2 pneumonia, 347 met inclusion and exclusion criteria and were enrolled in the study. The NOT-REC patients (n=24; 6.9%) were significantly older [67 (62–76) vs. 63 (53–71) years; p=0.02], more frequently current smokers [4 (17%) vs. 12 (4%); p=0.02] and with more severe respiratory failure at the time of hospitalization [PaO2/FiO2 at admission: 201 (101–314) vs. 295 (223–343); p=0.01] compared to REC group (n=323; 93.1%). On multivariable analysis, being a current smoker resulted in an independent predictor for lung sequelae after 12 months from hospitalization [5.6 OR; 95%CI (1.41–22.12); p=0.01]. Conclusions: after 12 months from hospital admission, a limited number of patients displayed persistent pulmonary sequelae with minimal extension. Being a current smoker at the time of SARS-CoV-2 infection is an independent predictive factor to lung consequences, regardless of the disease severity.